TECHNOLOGY FOR INCLUSIVE ARABIC LANGUAGE EDUCATION: ADDRESSING THE NEEDS OF SPECIAL EDUCATION ARABIC LEARNERS - Wahyuni; Hassan Ali; Adam Idris (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Inclusive education has gained increasing attention as a critical factor in ensuring all students, including those with special educational needs, have access to quality learning experiences. Arabic language education, in particular, presents unique challenges for special education learners due to its complex script, grammar, and phonology. Technology has been suggested as a solution to support these learners by providing tailored, adaptive learning experiences. This study investigates the role of technology in enhancing Arabic language learning for special education students. The research aims to identify how assistive technologies, such as text-to-speech tools, interactive apps, and gamified learning environments, can improve both student engagement and language proficiency. A mixed-methods approach was employed, including pre- and post-test assessments of language proficiency, a student engagement survey, and qualitative interviews with students and teachers. The findings indicate that the experimental group, which utilized technology-enhanced tools, showed significant improvements in language proficiency and higher levels of engagement compared to the control group using traditional methods. This study concludes that technology offers substantial benefits in creating more inclusive and effective Arabic language education environments for special education learners. The integration of adaptive learning technologies is essential for supporting students with disabilities and fostering their academic success.